2010
DOI: 10.1038/ijo.2010.54
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic or bariatric surgery? Long-term effects of malabsorptive vs restrictive bariatric techniques on body composition and cardiometabolic risk factors

Abstract: Background: Obesity is an increasing health problem and surgery seems to be the only treatment effective in achieving weight loss without relapse. Among bariatric techniques, many differences exist in terms of weight loss and resolution of comorbidities. Up to now, there are no prospective studies comparing long-term effects of malabsorptive vs restrictive techniques. Objective: In this study, cardiometabolic risk factors and body composition changes after malabsorptive biliointestinal bypass (BIBP) and restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
2
24
1
2
Order By: Relevance
“…The study noted that RYGB surgery produces a clear benefit in all lipid fractions [34]. In contrast, previous studies with restrictive surgery techniques have reported no significant difference in total cholesterol levels [35][36][37]. We observed mean decrease of 71.1 mg/dL in total cholesterol after 1 year of [35,39,40].…”
Section: Discussioncontrasting
confidence: 79%
“…The study noted that RYGB surgery produces a clear benefit in all lipid fractions [34]. In contrast, previous studies with restrictive surgery techniques have reported no significant difference in total cholesterol levels [35][36][37]. We observed mean decrease of 71.1 mg/dL in total cholesterol after 1 year of [35,39,40].…”
Section: Discussioncontrasting
confidence: 79%
“…HDL seems to be increased with most procedures 35,56 , similar to reduction of inflammatory mediators 83 .…”
Section: The Choice Of Bariatric Surgerymentioning
confidence: 92%
“…Studies showing prevention of CV events and CV mortality are lacking for other bariatric procedures such as sleeve gastrectomy and BPD, even though the latter is associated with important reduction of CV risk factors [32][33][34][35][36][37][81][82][83] . A number of alternative procedures to bariatric surgery, such as intragastric balloons, and endobarriers, has been evaluated in short term studies.…”
Section: The Choice Of Bariatric Surgerymentioning
confidence: 98%
“…Laparoscopic adjustable gastric banding (LAGB) is a restrictive comparable procedure, reversible and showing a very low rate of complication. 20 Previous data demonstrated that genetic factors, such as À174G4C IL-6 polymorphism, which have an important role in the regulation of body weight (BW), may account for differences in the therapeutic response to LAGB. 21 Because of several, but not really exhaustive, data regarding the relevance of IL-6 on body composition and adipose tissue homeostasis regulation, we investigated the role of À174G4C IL-6 polymorphism on the efficacy of weight loss, body composition and fluid distribution changes in obese subjects, evaluated by dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance analysis (BIA), at 6 months follow-up after LAGB surgery.…”
Section: Introductionmentioning
confidence: 99%